The Importance of Team Approach in Social Work - Vaicekauskienė, Violeta (Socialinė teorija, empirija, politika ir praktika, 2001)
The specialists from municipalities, day care and occupation organisations and institutional care organisations were participating in the discussion about the role of teamwork in social work practice. The participants were divided in to several groups and there the practise of teamwork took place.
Keywords: Teamwork; Social work; Discussion